Industrial Activity Land Suitability Assessment Using Delphi and AHP to Control Land Consumption¨: The Case Study of Bordj Bouarreridj, Algeria - Benaissa, F. T.; Khalfallah, B. (Engineering, Technology & Applied Science Research, 2021)
Studies and research on land suitability for the localization of economic and industrial activities in cities are attracting academics and local policies concerned with urban planning and organization in order to make urban areas more accommodating. The current paper aims to demonstrate the ability of visualization and simulation techniques to assist planners in preserving urban real estate by combining the Delphi method with one of the multi-criteria hierarchical analysis decision-making techniques. The city of Bordj Bouarreridj in Algeria was chosen as the case study and, with the participation of experts, a set of criteria were adopted to determine land suitability. Three criteria were selected in the first phase with the use of the Delphi method. In the second phase, we applied the Analytical Hierarchy Process (AH, a hierarchical analysis method. During the third stage, the obtained results were translated into the GIS program to derive the spatial suitability map. The following are among the most important achieved results: 13.38% (521.793 km2) of the area was regarded to be of high suitability, 67.54% (2,634.758 km2), achieved moderate suitability, 12.94% (504,794 km2) attained low suitability, and 6.14% (239,685 km2) were found to be not suitable at all.